Khazanah Ajaran Tasawuf Nusantara: Respon Terhadap Krisis Kemanusiaan di Era Kontemporer - Hajam; Theguh Saumantri (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
This study aims to explore the relevance and contribution of Nusantara Sufism teachings in addressing the humanitarian crises faced by contemporary society. The research method used is descriptive qualitative with a library research approach. Data were collected from various relevant literature, including books, journals, articles, and digital sources discussing Nusantara Sufism teachings and humanitarian crises. Data analysis was conducted qualitatively by identifying main themes that emerged from the literature and evaluating the contributions of these teachings in the context of humanitarian crises. The findings indicate that Nusantara Sufism teachings can provide concrete solutions to humanitarian crises through the harmonization of spiritual and material dimensions. The teaching of Manunggaling Kawula Gusti encourages the search for deeper meaning in life, reducing the spiritual emptiness that often underlies various crises. Pepatah Petitih offers moral values that can guide ethical behavior in society, while Sangkan Paraning Dumadi provides a philosophical framework for understanding and accepting the journey of life. The theoretical implications highlight the importance of integrating spiritual dimensions in the study of humanitarian crises and open opportunities for further research on the contribution of local teachings in solving global issues.